Sebastiania Chamaelea (L.) Mull. Arg. - An Experimental Study for Analgesic Efficacy - Thomas, Honey; Ansary, P Y; Shincymol , V V; Oommen, Sara Monsy (International Research Journal of Ayurveda & Yoga, 2023)
The recognition of pain as a pathologic phenomenon in and of itself is still up for discussion. Despite the evidence that pain is an illness, the pathologic nature of this condition has not yet been fully acknowledged. In order to fulfil the growing need for pain management, this study sought to improve the native flora. Sebastiania chamaelea (L.) Mull.Arg, is one among those indigenous flora of Kerala that was in folklore management of ailments decades back. In the study, the analgesic efficacy of whole-plant powder was evaluated in Wistar albino rats using the Eddy’s Hot plate method at three distinct doses (effective dose, half the effective dose, and double the effective dose). The outcome variable under investigation was the duration of jumping or licking paws. The drug’s analgesic activity is evidenced by the lengthening of the response time. One-way ANOVA was performed on the collected data along with a Tukey post-hoc test. According to the findings, the double dosage group of rats had significant analgesic effect when compared to other dose groups and the control group at a P value < 0.005. and the double-dose group had the longest time for reaction at the 60th minute (p<0.0001). The powder form of the drug showed considerable analgesic action at its double the effective dose when evaluated using the thermal model of Wistar albino rats, also known as the Eddy’s hot plate method.